Corporate Sustainability Disclosure Practices In Bangladesh: A Comparison Of Two Banks From An Institutional Perspective - Sobhani, Farid Ahmad (2011)

(untitled)
Sustainability is now a global concern because of the effects of climate change, social unrest, and economic depression. This has encouraged the corporate bodies to be accountable by disclosing their sustainability activities that may affect the earth and society at large. The study aims to focus on the extent of corporate sustainability disclosure (CSD) practices, and identification of the factors behind the disclosure and nondisclosure of CSD information by two selected banks in Bangladesh.